Traces of Nidhal Guessoum's Thought:a Monument to the Integration of Modern Islamic Education - Halim, Abdul; Sumianti; Jamil, Helmun; Saputra, Muhammad Beni (Al-Hayat: Journal of Islamic Education, 2024)
This study attempts to find the basic principles proposed by Guessoum in harmoniously combining religious knowledge and modern science without sacrificing the essence of both. This study uses a qualitative method with a literature study type of research. Primary data sources are quoted from Nidhal Guessoum's thoughts through several relevant books and journals. At the same time, secondary data is quoted through online media searches such as Sinta, Scopus, Google Scholar, DOAJ, Garuda, Mendeley, Emerald Insight, ScienceDirect, and other media. Data collection techniques use documentation techniques with literature studies from various literature and media, such as books, journal articles, etc. Data is collected and categorized, inventoryed, and analyzed critically. The data analysis technique used is content analysis, which includes descriptions and implications. Content analysis provides description, verstehen, interpretation, holistic and reflection. The study results show Guessoum's traces of thought, monuments to integrating modern Islamic education, emphasize an inclusive and comprehensive approach. Guessoum stresses the importance of engaging students in an active learning process and allowing them to develop a deep understanding of Islamic teachings. Guessoum's contributions to modern Islamic education cover many aspects, from integrating religion and science to applying Islamic values ​​in social and global contexts. Guessoum emphasized the need for the integration of faith and science. Guessoum believes Islamic education teachesligious doctrines but includes humanitarian, scientific, cultural, justice, equality, and peace values.